Endoscopic management of recurrent tracheoesophageal fistula induced by chronic use of nonsteroidal anti-inflammatory drugs: A case report and review of the literature - Voiosu Theodor Alexandru; Gheorghe Andrada Viorela; Bobeica Dan Adrian; Voiosu Andrei Mihai; Mateescu Radu Bogdan (Romanian Journal of Internal Medicine, 2018)
Tracheoesophageal fistula (TEF) is frequently congenital and requires surgical correction. TEF can also occur secondary to malignant esophageal tumors or benign diseases and these cases are managed by endoscopic means, such as closing the defect with metallic stents. Although esophageal injury can occur secondary to nonsteroidal anti-inflammatory drugs (NSAIDs), TEF secondary to chronic NSAIDs use has not been described in the literature.